Communicate, debug and trust：Study on the adaptive level of patient communication in the era of intelligent communication (The Journal of Medicine, Humanity and Media, 2024)
In the era of intelligent communication, various social relations are constantly reshaped and the structure and position of subject and object in the previous relationship models are changed. The doctor-patient relationship observed in this paper is not only affected by the ubiquitous relationship reconstruction, but also may cause relationship risks and trust crises due to the professional knowledge gap in the communication process, and even lead to extreme emotions and behaviors in the process of doctor-patient communication. At the same time, the intelligent media platform has become a "key factor" in the establishment of a new doctor-patient relationship in the intelligent era. Based on the above, this study attempts to establish a measurement tool for patient communication adaptability to respond to whether the trust mechanism of doctor-patient communication has a good debugging effect on the establishment and maintenance of doctor-patient relationship under the dual role of field change and knowledge empowerment.
Keywords: Patient communication adaptability; Multiple subject; Trust